How will South Africa's mandatory salt reduction policy affect its salt iodisation programme? A cross-sectional analysis from the WHO-SAGE Wave 2 Salt & Tobacco study. Issue 3 (30th March 2018) - Charlton, Karen; Ware, Lisa Jayne; Baumgartner, Jeannine; Cockeran, Marike; Schutte, Aletta E; Naidoo, Nirmala; Kowal, Paul
Abstract : Objective: The WHO's global targets for non-communicable disease reduction recommend consumption of<5 g salt/day. In 2016, South Africa was the first country to legislate maximum salt levels in processed foods. South Africa's salt iodisation fortification programme has successfully addressed iodine deficiency but information is dated. Simultaneous monitoring of sodium reduction and iodine status is required to ensure compatibility of the two public health interventions. Design/setting/participants: A nested cohort design within WHO's 2015 Study on global AGEing and adult health (n=2887) including individuals from households across South Africa. Randomly selected adults (n=875) provided 24-hour and spot urine samples for sodium and iodine concentration analysis (the primary and secondary outcome measures, respectively). Median 24-hour urinary iodine excretion (UIE) and spot urinary iodine concentrations (UIC) were compared by salt intakes of <5g/day, 5–9g/dayand >9 g/day. Results: Median daily sodium excretion was equivalent to 6.3 g salt/day (range 1–43 g/day); 35% had urinary sodium excretion values within the desirable range (<5 g salt/day), 37% had high values (5–9 g salt/day) and 28% had very high values (>9 g salt/day). Median UIC was 130 µg/L (IQR=58–202), indicating population iodine sufficiency (≥100 µg/L). Both UIC and UIE differed across salt intake categories (p<0.001) and were positively correlated with estimated salt intake (r=0.166 and 0.552, respectively; both p<0.001). Participants with salt intakes of <5 g/day were not meeting the Estimated Average Requirement for iodine intake (95 µg/day). Conclusions: In a nationally representative sample of South African adults, the association between indicators of population iodine status (UIC and UIE) and salt intake, estimated using 24-hour urinary sodium excretion, indicate that low salt intakes may compromise adequacy of iodine intakes in a country with mandatory iodisation of table salt. The iodine status of populations undergoing salt reduction strategies needs to be closely monitored to prevent re-emergence of iodine deficiency.